How droplets nucleate and grow on liquids and liquid impregnated surfaces. Issue 1 (20th November 2014) - Anand, Sushant; Rykaczewski, Konrad; Subramanyam, Srinivas Bengaluru; Beysens, Daniel; Varanasi, Kripa K.
Abstract : Condensation on subcooled liquids is most likely to occur at the liquid–air interface. On cloaking liquids, droplets are instantaneously cloaked post-nucleation, get submerged, and this cycle starts afresh. Viscosity of the liquid plays the main role in droplet growth. Abstract : Condensation on liquids has been studied extensively in context of breath figure templating, materials synthesis and enhancing heat transfer using liquid impregnated surfaces. However, the mechanics of nucleation and growth on liquids remains unclear, especially on liquids that spread on the condensate. By examining the energy barriers of nucleation, we provide a framework to choose liquids that can lead to enhanced nucleation. We show that due to limits of vapor sorption within a liquid, nucleation is most favoured at the liquid–air interface and demonstrate that on spreading liquids, droplet submergence within the liquid occurs thereafter. We provide a direct visualization of the thin liquid profile that cloaks the condensed droplet on a liquid impregnated surface and elucidate the vapour transport mechanism in the liquid films. Finally, we show that although the viscosity of the liquid does not affect droplet nucleation, it plays a crucial role in droplet growth.